Confirmatory factor analysis of the Neuropsychological Assessment Battery of the LADIS study: a longitudinal analysis - Moleiro, C.; Madureira, S.; Verdelho, A.; Ferro, J. M.; Poggesi, A.; Chabriat, H.; Erkinjuntti, T.; Fazekas, F.; Hennerici, M.; O'Brien, J.; Pantoni, L.; Salvadori, E.; et al. (Journal of Clinical and Experimental Neuropsychology, 2013)
Age-related white matter changes have been associated with cognitive functioning, even though their role is not fully understood. This work aimed to test a 3-factor model of the neuropsychological assessment battery and evaluate how the model fit the data longitudinally. Confirmatory factor analysis (CFA) was used to investigate the dimensions of a structured set of neuropsychological tests administered to a multicenter, international sample of independent older adults (LADIS study). Six hundred and thirty-eight older adults completed baseline neuropsychological, clinical, functional and motor assessments, which were repeated each year for a 3-year follow-up. CFA provided support for a 3-factor model. These factors involve the dimensions of executive functions, memory functions, and speed and motor control abilities. Performance decreased in most neuropsychological measures. Results showed that executive functioning, memory and speed of motor abilities are valid latent variables of neuropsychological performance among older adults, and that this structure is relatively consistent longitudinally, even though performance decreases with time.